The Effect of Training and Development on Teacher Performance Mediated by Readiness to Change During COVID-19 Pandemic - Laela Azizatur; Sandra Irawati; Novi Puji Lestari (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to determine the effect of training and development on teacher performance and is mediated by a readiness to change during the covid 19 pandemic. The type of research used is Explanatory Research or survey research methods. Data was collected by distributing questionnaires. The number of questionnaires distributed was 38 teachers at the Salsabila Foundation. Testing the instrument in this study uses validity and reliability tests where the results of the questionnaires that have been distributed are valid and reliable. The results of the classical assumption test in this study are Normal distribution and there are no symptoms of multicollinearity and heteroscedasticity. The results of this study indicate that training and development affect teacher performance through readiness to change. It can be concluded that readiness to change can mediate between training and development on teacher performance at the Salsabila foundation.